PRCA with myelofibrosis: an unusual case report - Kar, Rakhee (Springer-Verlag, 2008)
The association of PRCA and myelofibrosis is very rare with only two such cases reported in the literature. Leukemic transformation in myelofibrosis is known but the progression of PRCA to acute leukemia is very rare. We present an unusual case of PRCA with myelofibrosis which after 14 months of transfusion dependent anemia transformed to acute monocytic leukemia.